Modbus Packet Analysis and Attack Mode for SCADA System - Cheng-Hui Chou; Chi-Che Wu; Kuan-Chu Lu; I-Hsien Liu; Tien-Hsiang Chang; Chu-Fen Li; Jung-Shian Li (Journal of ICT, Design, Engineering and Technological Science, 2018)
Internet of Things (IoT) and Industry 4.0 have become more and more common in recent years. In fact, smart houses that are common in the home, also include the monitor of the factory. Numerous IoT devices are developed on the basis of Linux. In view of this traditional network installation is more worthy of attention on the IoT. We remember to update the update of the home computer but often overlook the update of the IoT device because most of the IoT devices requires manual updates. Hackers often exploit this vulnerability to attack related devices. So, how to protect the IoT equipments is the topic of this study. This study proposes a honeypot search system based on self-study. The system can be used to search the honeypot system that may exist in the regional network, and design a smart honeypot system to confuse the attack of the hacker and protect the internal system of the enterprise.